Problem Based Learning Strategy Based on Local Wisdom in PAI Learning in Bima - Junaidin Junaidin (FiTUA: JURNAL STUDI ISLAM, 2025)
Using a mixed-method approach with an exploratory-sequential model, this study combines literature review and a VARK-based learning style survey of 43 Generation Z respondents, consisting of university students and students from state senior high schools. This study aims to examine the Problem-Based Learning (PBL) strategy integrated with local wisdom values in the context of Islamic Religious Education (IRE) in Bima, West Nusa Tenggara. Using a mixed-method approach with an exploratory-sequential model, this study combines literature review and a VARK-based learning style survey of 43 Generation Z respondents. The results indicate that integrating PBL with local values such as Nggahi Rawi Pahu, Maja Labo Dahu, and Ngaha Aina Ngoho strengthens contextual learning that supports the reflective and participatory internalization of Islamic values. The dominant learning styles are auditory and multimodal, aligning with the characteristics of PBL, which is based on discussion, collaboration, and real-world problem-solving. Additionally, the use of digital technologies like Canva and podcasts enhances digital literacy and active student engagement. These findings emphasize the importance of developing adaptive PAI strategies that align with local culture and the learning characteristics of Generation Z.